The Politics of Migration in Indonesia and Beyond - Tirtosudarmo, Riwanto (Springer Singapore, 2018)
This book looks at migration from social and political dimensions, placing its studies between the realm of demography and politics. It approaches the issues of migration by emphasizing the important power relations that have been neglected in the study of migration. The book starts by looking at Indonesian migration to provide an understanding of internal migration. It then looks beyond its national borders for a wider understanding of Asia. This book showcases several case studies both in Indonesia and beyond to illustrate the intricate politics of migration. It also looks at the politics of migration from the sending country perspective and unravels the link between migration and security. The book provides reviews of the wider literature relating to population mobility and distribution. It also shows readers how to adopt a new perspective in the study of movement of people, which is an issue that is increasingly becoming important as movement of people unfolds globally in terms of both volume and direction. This book is a valuable asset for students, academics and researchers in the area of demography and social-politics, especially those interested in migration and refugees. Those keen in understanding decentralization in greater depth will also benefit from this book. .